Law Enforcement Against Document Forgery in the Field of Taxation - Jiwar, Syarif (Journal of Posthumanism, 2025)
The tax collection system that applies in Indonesia is a self-assessment system, where taxpayers are given the trust to calculate and pay their taxes owed. In the implementation of the self-assessment system, conflicts arise due to differences of opinion between taxpayers and tax authorities. These differences are often utilized by taxpayers to take advantage of legal loopholes by committing tax crimes, one of which is by falsifying tax documents such as falsification of tax invoices, falsification of bookkeeping or recording of financial report, forgery of stamps, submitting or reporting tax return whose contents are incorrect or incomplete. In order to deal with tax crimes and uphold the principle of the self-assessment system in the Indonesia tax system, as well as to increase tax compliance of taxpayers, tax law enforcement is carried out through tax audits, tax investigations, and tax collection